Comparison of smart specialization in coastal regions in Poland - Jacek Soltys; Dorota Kamrowska-Zaluska (European Regional Science Association (ERSA), 2016)
The priorities set by the European Commission for Programming Period 2014-2020 introduced new instruments supporting regional development but also posed new requirements that must be met by European regions. One of them is smart specialization. To implement Strategy for Europe 2020, published by the European Commission in 2010, EU Member States and their regions develop strategies for smart specialization that will show directions for providing support to the strengthening of research, development and innovation. Smart specialization is an important instrument for creating a strategy for the development of innovation at the state and regional level as well as for defining and building the knowledge-based economy. This paper presents analyzes of processes responsible for identifying smart specialization in West Pomeranian and Pomeranian Regions. This article is a continuation and extension of the research on the process of emergence of smart specialization in Pomeranian Region by the inclusion of the West Pomeranian Region into this study. Both Regions are situated on the southern coast of the Baltic Sea and are seats of main Polish harbours and shipyards. Their regional capitals Gdansk and Szczecin are emerging metropolitan areas as well as economic engines of polish economy. It is our goal to analyze to what extent emergence of smart specialization is helping to focus development of innovation in areas consistent with their endogenous potentials. The aims of the paper are: comparison of the areas of smart specialization with particular emphasis on the specifics of the seaside location and endogenous potential of both regions, comparison of emergence and the process of selection of smart specialization, including its evaluation. In Pomeranian region the process of emergence of smart specialization was a bottom-up one where Regional Government invited all actors to build a partnership. The result is participation of all stakeholders to identify opportunities and specify areas of development of smart specializations for the Voivodship. In other regions of Poland it was more of a top-down process, conducted by experts and the West Pomeranian Region is an example of this approach. Methodology of the research applied for this study is desk research (analysis of literature, documents and strategies from Voivodeship Marshal Offices from both West Pomeranian and Pomeranian Regions), individual in-depth interviews, participation in the process of emerging of smart specialization in Pomorskie Voivodeship (focus group interviews, workshops, SWOT analysis and Delphi study) and comparative analysis of the process of emergence and selection of the smart specialization in both regions.
Keywords: O2; O3; O38; 330; smart specialization; coastal regions; maritime economy; regional knowledge-based development; innovation strategy